"Can I go to Glasgow?" Learnings from patient involvement at the 17th Congress of the International Society for Peritoneal Dialysis (ISPD). Issue 1 (January 2020) - Gutman, Talia; Manera, Karine E; Baumgart, Amanda; Johnson, David W; Wilkie, Martin; Boudville, Neil; Craig, Jonathan C; Dong, Jie; Jesudason, Shilpa; Mehrotra, Rajnish; Neu, Alicia; Shen, Jenny I; et al.
Background: Recognition of the discrepancy between the research priorities of patients and health professionals has prompted efforts to involve patients as active contributors in research activities, including scientific conferences. However, there is limited evidence about the experience, challenges, and impacts of patient involvement to inform best practice. This study aims to describe patient and health professional perspectives on patient involvement at the Congress of the International Society for Peritoneal Dialysis (ISPD). Methods: Semi-structured interviews were conducted with 14 patients/caregivers and 15 health professionals from six countries who attended ISPD. Interviews were recorded and transcribed verbatim, and transcripts were analyzed thematically. Results: We identified four themes: protecting and enhancing scientific learning (grounding science in stories, sharing and inspiring new perspectives, distilling the key messages of research presentations, striking a balance between accommodating patients and presenting the science); democratizing access to research (redistributing power, challenging the traditional ownership of knowledge, cultivating self-management through demystifying research); inadequate support for patient/caregiver delegates (lacking purposeful inclusion, challenges in interpreting research findings, soliciting medical advice, difficulty negotiating venue and program, limited financial assistance in attending); and amplifying impact beyond the room (sparking innovation in practice, giving patients and families hope for the future). Conclusions: Patient involvement at the ISPD Congress clarified the applicability of research to patient care and self-management, democratized science, and strengthened the potential impact of research. More structured support for patients to help them purposefully articulate their experience in relation to session objectives may enhance their contribution and their own learning experience.